Inflammatory Biomarkers in Tissue Remodeling and Fibrosis Progression: Biomarker Inflamasi dalam Remodeling Jaringan dan Perkembangan Fibrosis - Abbas, Marwa Ismail (Indonesian Journal on Health Science and Medicine, 2025)
Background; Inflammatory biomarkers play a crucial role in tissue remodeling and fibrosis progression by mediating the inflammatory response and influencing extracellular matrix deposition. Aims of the study; Investigate the role of inflammatory biomarkers in tissue remodeling and the progression of fibrosis. Methodology; A case-control study of 90 patients, conducted from November 1, 2024, to February 1, 2025, aimed to examine the role of inflammatory biomarkers in tissue remodeling and fibrosis progression. The study included 60 patients diagnosed with fibrosis and 30 healthy controls. Blood samples were collected, processed, and analyzed for biomarkers (CRP, IL-6, IFN-γ, MCP-1, adiponectin) using ELISA. Fibrosis severity was assessed using FibroScan elastography and histopathology with Masson's trichrome stain to evaluate collagen deposition. These methods helped correlate systemic inflammatory biomarker levels with fibrosis progression. Result; The study showed no significant age difference between patients with tissue fibrosis (48.6 ± 10.4 years) and controls (47.2 ± 9.8 years, p = 0.52). However, patients had significantly higher BMI (27.8 ± 3.5 kg/m², p = 0.01) and a higher smoking rate (38%, p = 0.03). Inflammatory markers, including CRP, IL-6, IFN-γ, and MCP-1, were significantly elevated in patients. Adiponectin levels were lower (7.8 ± 1.9 μg/mL, p < 0.001). Strong correlations were found between inflammatory markers and fibrosis severity, with MCP-1 showing the strongest association. Conclusions; The study concluded that elevated inflammatory markers (CRP, IL-6, IFN-γ, MCP-1) and decreased adiponectin levels are strongly associated with tissue fibrosis progression. The inflammatory response, characterized by these biomarkers, promotes fibrosis through immune activation and tissue remodeling. Adiponectin's protective role against inflammation and fibrosis underscores its potential as a therapeutic target. Highlights: Biomarker Impact: Elevated CRP, IL-6, IFN-γ, and MCP-1 levels correlate with fibrosis severity. Protective Role: Lower adiponectin levels suggest its antifibrotic potential. Clinical Relevance: MCP-1 shows the strongest association, making it a key fibrosis indicator. Keyword: Inflammatory Biomarkers, Tissue Remodeling, Fibrosis Progression, CRP, Adiponectin, MCP-1